Dual panel multiplex PCR assay for rapid detection of medically important fungi and resistant species of Candida and Aspergillus - Mohd Hanif Jainlabdin,; Ang, Lim Chua; Tzar Mohd Nizam Khaithir,; Jacinta Santhanam, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Invasive fungal infections (IFIs) have risen dramatically in recent years among high risk immunocompromised patients. Rapid detection of fungal pathogens is crucial to timely and accurate antifungal therapy. Two multiplex polymerase chain reaction (PCR) assays were developed to detect major fungal species that cause invasive infections and identify resistant species. Genus specific primers for Candida, Aspergillus, Fusarium and species specific primers for Candida glabrata, Candida krusei and Aspergillus terreus which are known to be clinically resistant species, were designed from the internal transcribed spacer (ITS) regions of ribosomal ribonucleic acid (rRNA) gene complex. Both assays were performed simultaneously to promote rapid detection of fungal isolates based on distinct amplicon sizes. Inclusion of the universal fungal primers ITS 1 and ITS 4 in the genus specific assay produced a second amplicon for each isolate which served to confirm the detection of a fungal target. The limit of detection for the genus specific assay was 1 nanogram (ng) deoxyribonucleic acid (DNA) for Aspergillus fumigatus and Candida albicans, 0.1 ng DNA for Fusarium solani, while the species-specific assay detected 0.1 ng DNA of A. terreus and 10 picogram (pg) DNA of C. krusei and C. glabrata. The multiplex PCR assays, apart from universal detection of any fungal target, are able to detect clinically important fungi and differentiate resistant species rapidly and accurately, which can contribute to timely implementation of effective antifungal regime.